Profitability Analysis of Markets Traded on Borsa Istanbul - Dayı, Faruk; Adaiem, Nasreddin (Journal of the Human and Social Sciences Researchers, 2024)
Supermarkets significantly increased product prices in response to the sudden and sharp rise in the exchange rate in July 2018. A similar situation unfolded in 2021 when interest rates dropped, and the exchange rate experienced a steep increase. The surge in demand for foreign currency and subsequent interest rate cuts led to an escalation in the exchange rate. Consequently, production costs rose due to inflated raw material prices, resulting in higher product prices. Additionally, supermarkets allegedly engaged in cartel-like behavior, purposely withholding products from sale, further contributing to price hikes between 2021 and 2022. This study evaluates whether supermarkets garnered substantial profits during the period. Financial statement data from 2018 to 2022 was analyzed using vertical, trend, and ratio analyses to assess the financial position and profitability of five companies listed on Borsa Istanbul. Throughout the 2018-2022 period, except for 2022, BIM demonstrated the highest return on assets ratio. The return on assets ratios for 2022 and 2021 exhibited an upward trend, indicating an increase in profitability during 2022. SOK recorded the highest return on equity ratio in the 2018-2022 period, while CarrefourSA reported the lowest. Furthermore, the companies witnessed notable growth in revenues, gross sales profitability, and net profitability in 2022, surpassing previous years. This suggests they earned more profit by increasing prices at a greater rate than their costs in 2022. The operating profitability of the companies also experienced an upswing during this period. BIM held the largest share of operating profit in revenues in 2022, while CarrefourSA possessed the smallest share. In terms of net profitability, the companies fared better in 2022 compared to 2021, with net profitability exhibiting a more substantial increase during 2022.
Keywords: 8. Economic growth; 1. No poverty